Mauriac en une, Mauriac en livre, Mauriac en ligne. Réflexion sur les dispositifs éditoriaux - Philippe Baudorre; Jessica de Bideran (Humanités Numériques)
In an era when writing and reading converge in the same digital environment, we would like to think about the digitisation of the literary heritage and about the reading contexts that we are building. This paper proposes a reflection on textual migrations and more particularly on the displacement of “press” productions to another, digital medium.